Application of quality control circle activities to reduce the incidence of aspiration in patients with dysphagia after stroke (降低脑卒中吞咽困难患者误吸发生率的品管圈实践) - MA Xin (马欣); WANG Li (王丽); HUANG Chaoping (黄朝萍); ZHANG Shuai (张帅); GENG Qingwen (耿庆文) (中西医结合护理)
Objective To evaluate the quality control circle (QCC) activities in reducing the incidence of aspiration in patients with dysphagia after stroke. Methods A QCC group was set up, and a series of activities based on QCC theory were carried out including theme identification, plan making, status investigation, factor analysis, countermeasures and implementation. An analysis of aspiration condition in 80 patients with dysphagia after stroke was carried out after implementation of QCC activities (between April and October 2019), and the incidence of aspiration was compared with that of 80 patients recruited before implementation of QCC activities (between February and June 2017). Results The incidence of aspiration decreased from 25. 00%(20/80)to 5. 00%(4/80), with a target achievement ratio of113. 64 and progress ratio of 80. 00%. Nurses' comprehensive ability was enhanced after implementation of QCC activities. Conclusion The QCC is effective to reduce the incidence of aspiration in patients with dysphagia after stroke. (目的 探讨品管圈活动降低脑卒中吞咽困难患者误吸发生率的效果。方法 成立品管圈活动小组, 按照品管圈理论进行主题选定、活动计划、现状把握、要因分析、对策拟定与实施等活动, 分析2019年4月—10月(品管圈活动开展后)科室收治的脑卒中吞咽障碍住院患者80例的误吸发生情况, 并与2017年2月—6月(品管圈活动开展前)科室收治的80例脑卒中吞咽障碍住院患者的误吸发生情况进行对比。结果 脑卒中吞咽障碍住院患者误吸发生率由品管圈活动开展前的25. 00%(20/80)降低至品管圈活动开展后的5. 00%(4/80), 活动目标达成率113. 64% , 进步率80. 00%, 护士综合能力也得到提高。结论 开展品管圈活动能够降低脑卒中吞咽困难患者误吸发生率, 有利于提高护理质量。)